Talk by Chairman of the Board of Trustees (Institutional Knowledge at Singapore Management University, 2000)
Faculty and the pioneer class of Singapore Management University undergraduates at talk by Ho Kwon Ping, Chairman of the Board of Trustees. He gave students an account of his personal life and corporate experiences. The talk was held at the Singapore Art Museum on 19 July 2000. Front row, left to right: President Janice Bellace, Deputy President Tan Teck Meng, Provost Tan Chin Tiong and Professor Augustine Tan.